Does an extended mediastinal lymphadenectomy improve outcome after R0 resection in lung cancer? - Wu, Nan; Yan, Shi; Lv, Chao; Li, Shaolei; Feng, Yuan; Wang, Yuzhao; Wang, Jia; Zheng, Qingfeng; Yang, Yue (Chinese Journal of Cancer Research, 2014)
Objective: This retrospective study was conducted to investigate the impact of more extended mediastinal lymphadenectomy on the outcome of lung cancer patients treated with R0 resection. Methods: During the investigation period, 325 lung cancer cases were enlisted and 278 cases entered the analysis. The patients were divided into Control group (n=116) and Research group (n=162) according to the different extents of mediastinal lymph node clearance at different time periods. Three major parameters were retrospectively assessed to compare the quality of surgical care: extent of lymph node clearance, resection volume, and postoperative recovery process and common complications. Comparison of the outcome between two groups was carried out. Results: Research group showed a significant quality improvement of lymphadenectomy, such as more mediastinal node stations investigated (more than 3 N2 stations investigated: Research group, 90.7% vs. Control group, 55.2%; P=0.001) and more nodes collection (total nodes 26.1±10.0 vs. 19.1±8.3, P=0.000; N2 nodes 15.5±7.2 vs. 9.8±5.6, P=0.000). However, overall survival (OS) and disease-free survival (DFS) were not significantly different either between two groups (5-year OS: Control group, 56.4±4.6% vs. Research group, 62.6±4.3%; P=0.271) or between subgroups from stage I to IIIa. TNM stage and histology were significant factors associated with OS and DFS in multivariate analysis; extent of mediastinal lymphadenectomy was not associated with OS or DFS. Conclusions: More radical mediastinal lymphadenectomy may not lead to an improved oncological outcome for lung cancer treated with R0 resection.